Journal of the Academy of Marketing Science Official Publication of the Academy of Marketing Science - Hult, G. Tomas M.; Palmatier, Robert W.; Hulland, John.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of the Academy of Marketing Science (JAMS) is devoted to the study and improvement of marketing and serves as a vital link between scholarly research and practice by publishing research-based articles in the substantive domain of marketing. Manuscripts submitted for publication consideration in JAMS are judged on the basis of their potential contribution to the advancement of the science and/or practice of marketing. In order for a manuscript to be published in JAMS it must, at the minimum, meet the following criteria: Focus on a substantive issue in the domain of marketing Offer fundamentally new insights that advance the field Be literature-based and scholarly Demonstrate conceptual rigor Provide evidence of methodological rigor, if an empirical piece JAMS is committed to providing authors with: Timely and constructive reviews Specific and extensive directions (when necessary) for revising a manuscript A decision to either accept or reject a manuscript as early as possible in the review process The JAMS Editorial Office makes a concerted effort to ensure manuscript turnaround in fewer than 40 days. However, because JAMS is committed to ensuring that reviews are fair, informed, objective, and constructive, there may be occasional instances in which the turnaround time is longer.
Keywords: Business; Management science; Marketing; Social sciences; Business and Management, general; Marketing; Social Sciences, general